PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI ULANG YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA PRODUK SUSU CAIR DALAM KEMASAN SIAP MINUM MEREK ULTRA MILK DI KOTA BANDUNG - Shalsa Nur A; Edi Nurtjahjadi, SE., M.Si (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The purpose of this study to analyze the effect of product quality on repurchase intention mediated by customer satisfaction on liquid milk products in ready-to-drink packaging for the ultra milk brand in Bandung city. The findings in this study explain that the effectiveness of product quality on repurchase intention is through consumer satisfaction. This researchused approach of quantitative.The research instrument has gone through the stages of validity, reliability testing, classic assumption test, simple regression test, multiple regression test and sobel test.The instrument was used as a data collection tool respondents aged at least 18 years and over who have consumed ultra milk liquid milk in Bandung City which is the object assessed in this study. There were 150 respondents who participated in this study. The analytical tool used to test the instrument data is using SPSS software version 24 and Sobel Test. The results showed that: 1) Product quality has a positive and significant effect on customer satisfaction, 2) product quality has a positive and significant affects on repurchase interest, 3) customer satisfaction quality has a positive and significant effect on repurchase interest, 4) product quality has a positive and significant effect on repurchase interest mediated by customer satisfaction.